Development of Mobile Learning Media in Engineering Mechanics Subjects - Haryati, Sovia; Rizal, Fahmi; Syah, Nurhasan (Jurnal Edutech Undiksha, 2021)
Low student learning outcomes in Engineering Mechanics subjects require good learning media so that it is easier to understand the material and can be seen how it works repeatedly, namely with mobile learning media. Almost all students now have smartphones, so it is better if smartphones are used as learning media. The android application in this study contains material competencies, sample questions, learning videos and interactive evaluation questions. This study aims to analyze the increase in student learning outcomes by optimizing mobile learning media. The research method is a development research method. This research procedure uses a modified 4-D model development model. The study population was 62 students. The research sample was 31 students. The data collection method used is by giving a questionnaire. The instrument used was a questionnaire in the form of a Likert scale. The data analysis technique used is primary and secondary data. The results showed that the results of the validation carried out obtained an average percentage of 88% in the valid category, so it can be concluded that the mobile learning media application is valid for use in Engineering Mechanics learning